1984
DOI: 10.1042/bj2240755
|View full text |Cite
|
Sign up to set email alerts
|

Complement-component-C3-opsonized immunoglobulin G anti-DNA antibodies do not bind effectively to red blood cells unless aggregated on a high-Mr DNA matrix

Abstract: Large, soluble ds (double-stranded) DNA-IgG (immunoglobulin G) anti-dsDNA immune complexes (greater than or equal to 200 S) that were previously opsonized with complement were digested with DNAase. The small complement-component-C3-fragment-labelled IgG (11-14 S) that was then isolated did not bind effectively to complement receptor type 1 on human red blood cells. However, when this IgG was immune-complexed with 3H-labelled PM2 (bacteriophage directed against a marine Pseudomonas) dsDNA (Mr approximately 6 X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…showed that Immune complexes bound to both cell types with nearly equal avidity. The high binding constants we observed are consistent with previously published reports [13.28] and support the concept that the immune complex is a large multi-valent ligand which interacts with multiple receptors on the cell surface [28,34]. Despite the similarity in binding iividity.…”
Section: Discussionsupporting
confidence: 92%
“…showed that Immune complexes bound to both cell types with nearly equal avidity. The high binding constants we observed are consistent with previously published reports [13.28] and support the concept that the immune complex is a large multi-valent ligand which interacts with multiple receptors on the cell surface [28,34]. Despite the similarity in binding iividity.…”
Section: Discussionsupporting
confidence: 92%